Alliance formation in civil wars - Christia, Fotini (Cambridge University Press, 2012)
This book argues that relative power balances, rather than shared identities, explain why combatant groups in the Afghan civil wars constantly aligned with and double-crossed each other, and develops a theory on alliance formation and group fractionalization in multiparty civil wars.